STATE AND SOCIAL RESPONSE ON DOMESTIC VIOLENCE - Stajić, Ljubomir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Every violence encounters a certain reaction in society and in the state. Domestic violence as a form of violence causes a great public reaction, primarily because of its brutality, frequency and immorality. In addition, these consequences impact victims, the society and security system as a whole. Solving the problem of domestic violence requires a multidisciplinary approach. In this regard, the state undertakes range of measures and activities to prevent this violence. It also serves to suppress violence in the event of an outbreak. Primarily, these measures include implementation of appropriate strategic and legal acts, as well as the security measures and activities that overly define the competencies, organization, authorization and cooperation of certain state bodies and institutions. It has been noted that in the current research, the security aspects of domestic violence are not or have not been sufficiently explored. Taking into account the above, the paper analyzes consequences of domestic violence for both the victim and the security system, society and the state. New classifications of domestic violence have been completed, as well as the classification of models (patterns) of this violence. Also, the paper points to certain problems in the current state authorities' practice, primarily the police. Finally, the paper presents new solutions provided for in the Law on the Prevention of Domestic Violence, which serves to significantly improve, protect, and assist  victims' circumstances.